2003
DOI: 10.1021/ol030135k
|View full text |Cite
|
Sign up to set email alerts
|

Bolaforms with Fourteen Galactose Units:  A Proposed Site-Directed Cohesion of Cancer Cells

Abstract: [structure: see text] The multistep synthesis of a calixarene joined to a second calixarene via a long spacer is described. Since each calixarene bears multiple galactose-based units (known to bind strongly to rat hepatoma cells), there existed the possibility of cross-linking the cancer cells into a network. The compounds did not serve this purpose, a fact potentially correctable by adjusting or rigidifying the spacer. Formation of a "cancer net" around a solid tumor remains a viable approach to retarding gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…[33] The corresponding imidazole was synthesized according to a modified literature procedure. [34] 4,5-Dichloroimidazole (0.93 g, 6.8 mmol, 1 equiv) in THF (10 mL) was added to a suspension of NaH (0.27 g, 6.8 mmol, 1 equiv) in dry THF (50 mL) dropwise at 0 8C and left warming to ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[33] The corresponding imidazole was synthesized according to a modified literature procedure. [34] 4,5-Dichloroimidazole (0.93 g, 6.8 mmol, 1 equiv) in THF (10 mL) was added to a suspension of NaH (0.27 g, 6.8 mmol, 1 equiv) in dry THF (50 mL) dropwise at 0 8C and left warming to ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Because of their unique three-dimensional structure they have used as important tools for investigations in bioorganic chemistry and medicine [15][16][17][18]. The calixarenes were found to exhibit antibacterial activity against gram-positive and gramnegative bacterial strains [19][20][21], antiviral [22,23] and anticancer properties [24]. Finely, calixarenes can be used for biochemical recognition and separation of bioactive molecules such as amino acids, proteins, nucleotides, saccharides and steroids [25].…”
Section: калікс[4]арен α-гідроксифосфонові кислоти як потенційні інгіmentioning
confidence: 99%
“…This is an important research area as cooperative binding of a multivalent ligand to receptors on a single cell surface underpins the development of high avidity drugs (3), while the alternative binding mode, the crosslinking of cells by multivalent ligands, has been suggested as a new mechanism for biological intervention by multivalent drugs. The latter approach mimics the way that IgM forms large conglomerates of antigens that are easily opsonised by macrophages; indeed the use of multivalent ligands to form "cancer nets" around tumours and retard tumour growth has been suggested (4). Similarly, it has been suggested that the aggregation of other pathogens by synthetic multivalent polymers could form particles that are easier for the body to clear (5).…”
Section: (A) Vesicle Cross-linking By Polymers and Proteinsmentioning
confidence: 99%
“…Extensive phase separation is indicated by an E/M ratio greater than 0. 4 For initial studies, three standard payloads were selected for thermally triggered release from vesicle-nanoparticle assemblies; 5/6-carboxyfluorescein (5/6-CF), the potent anticancer drug methotrexate (MTX) and a fluorescently-tagged polysaccharide (4 kDa FITC-dextran). The alleviation of selfquenching caused by 5/6-CF release allows easy determination of release efficiency, while MTX is a non-fluorescent drug with a similar size.…”
Section: Thermally Sensitive Vesicle-nanoparticle Aggregatesmentioning
confidence: 99%